ANALYSIS OF SERUNI KOPI'S DIGITAL BUSINESS CONTENT IN INCREASING SALES TURNOVER - Aulya Fatahilla; Indira Fatra Deni Peranginangin; Deddy Parwis Jailani Nasution (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the use of Seruni Kopi's digital business content on Instagram as a marketing communication tool and its role in supporting increased sales turnover. This research departs from a gap in previous studies that tended to emphasize the role of social media in brand awareness and general promotion, while analysis of the function of digital content as a marketing communication instrument linked to sales turnover in local coffee MSMEs is still limited. The study used a qualitative approach with content analysis methods, supported by observations of the Instagram account @seruni.kopi, interviews with the business owner, and documentation of digital content. The results indicate that Seruni Kopi's digital content serves three main functions: conveying product information, building business image, and creating interaction with the audience through promotional content, shop atmosphere, and trend-based posts. The main finding of this study is that digital content contributes to a qualitative increase in visits and consumer response, but its effectiveness is not optimal because content management is still spontaneous and not strategically planned. Theoretically, this study emphasizes the importance of digital content as an interactive marketing communication medium for MSMEs. Practically, this study recommends the need for more consistent, varied, and targeted content planning to support optimal sales growth.